Determination of genetic relatedness in kelampayan plantlets regenerated from tissue culture using damd markers - Suthashinikisan, A/P Krishnan (Universiti Malaysia Sarawak, UNIMAS, 2013)
Neolamarckia cadamba and Neolamarckia macrophylla belongs to Rubiaceae family and locally known as white and red kelampayan respectively. They are economically important woody trees. These trees are large, deciduous and fast growing tree species. Most important of any in vitro propagation system is mass multiplication of plantlets that are genetically homogenous and phenotypically uniform. Modified CTAB method was used to extract the DNA. Directed amplification of Minisatellite-region DNA primers namely M13, YNZ, and 33.6 primers was used as a tool to assess the genetic relatedness of in vitro propagated N. cadamba and N. macrophylla hardened explants. The presence or absence of the amplification product showed allelic variation among individuals after visualizing as a band during electrophoresis. Cluster analysis of DAMD-PCR data using UPGMA (unweighted pair group method with arithmetic average) revealed the genetic relatedness among the species. A total of 21 bands and 24 bands were produced respectively. Mean gene diversity of N.cadamba and N.macrophylla is 0.1825 and 0.0926 respectively. Shannon index is 0.2632 and 0.1324 respectively. The low figure of both mean of gene diversity and Shannon index obtained shows that N. cadamba are related to each other while N. macrophylla samples are closely related. The UPGMA cluster analyses revealed N. macrophylla samples are highly related among the samples but two samples; MGR10-6 and MGR2- 2 belongs to different clones shows close relatedness. The close relatedness among the samples indicates that tissue culture generated samples of both the kelampayan species shows very little polymorphism and therefore in-vitro regenerated plantlets in this study maintain their genetic integrity.